Characterization and evaluation of potential impacts in the environment of residual fiber from cellulose - Zonta Neto, Alvaro João; Oliveira, Mariana Gomes; Skoronski, Everton; Alves, Maurício Vicente (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The search for final alternative destinations for residue from industrial processes is a growing problem. Pulp and paper industries generate large amounts of residue, which are not always reused or do not receive an adequate destination. An alternative is its reuse, using the final disposal of the residue in the soil, for its potential to inactivate part of the chemical compounds, allowing its use as agricultural inputs of low cost. The purpose of this study was to analyze the final residue of the wastewater treatment plant of a pulp and paper industry. Industries in this economic sector produce high resistance and low lignin cellulose pulp and recover the chemicals used, reducing costs. In order to pre-evaluate this disposal possibility, this study carried out the classification of the waste classifying the hazardousness of the cellulose fiber, and its behavior under solubilization and leaching tests. The results of the analysis showed the potential of solubilization of substances in water above the maximum permissible value (MPV), characterizing the residue as non-inert and non-hazardous Class IIA. This fact implies that safety doses must be evaluated before its application in soil. Further studies must be carried out in terms of toxicological effects and its potential to be applied to crops.